2014
DOI: 10.1039/c3ra46934d
|View full text |Cite
|
Sign up to set email alerts
|

Study of fibrinogen adsorption on poly(ethylene glycol)-modified surfaces using a quartz crystal microbalance with dissipation and a dual polarization interferometry

Abstract: Protein adsorption behavior is a key factor that determines whether materials can be used as medical polymer materials. In this study, fibrinogen (Fib) adsorptions on three different poly(ethylene glycol) (PEG) surfaces that differed in chain length and chain density were investigated using a quartz crystal microbalance with dissipation (QCM-D) and a dual polarization interferometry (DPI) with respect to adsorbed masses, viscoelastic properties and chain conformations. On QCM-D chips, PEG chains were tight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 53 publications
(56 reference statements)
2
28
0
Order By: Relevance
“…The tandem DPI/QCM-D has been recently applied to an interesting study about the adsorption of fibrinogen on surfaces coated with different poly(ethylene glycol) chains (Mw 1000, 2000 and 5000). 185 It was demonstrated that on QCM-D chips, polymer tight chains were in extended brush conformations, while on DPI chips, the two light chains collapsed to a pancake-like conformation but the heaviest one (5000) had a mushroom conformation. Fibrinogen completely extended on the relatively dense poly(ethylene glycol) 1000-modified DPI surface (0.10 chains/nm 2 ), but only partly on the poly(ethylene glycol) 2000-modified DPI surface (0.05chains/nm 2 ), and did not adsorb on the deformable and mushroom-shaped, poly(ethylene glycol) 5000.…”
Section: Polymer Interactionsmentioning
confidence: 99%
“…The tandem DPI/QCM-D has been recently applied to an interesting study about the adsorption of fibrinogen on surfaces coated with different poly(ethylene glycol) chains (Mw 1000, 2000 and 5000). 185 It was demonstrated that on QCM-D chips, polymer tight chains were in extended brush conformations, while on DPI chips, the two light chains collapsed to a pancake-like conformation but the heaviest one (5000) had a mushroom conformation. Fibrinogen completely extended on the relatively dense poly(ethylene glycol) 1000-modified DPI surface (0.10 chains/nm 2 ), but only partly on the poly(ethylene glycol) 2000-modified DPI surface (0.05chains/nm 2 ), and did not adsorb on the deformable and mushroom-shaped, poly(ethylene glycol) 5000.…”
Section: Polymer Interactionsmentioning
confidence: 99%
“…Most of these disadvantages can be eliminated by applying the quartz crystal microbalance with dissipation monitoring (QCM-D) technique that enables efficient, real time studies of protein adsorption and desorption at various substrates in liquid phases under flow conditions [16,[23][24][25][26][27][28]. However, a quantitative interpretation of these results is complicated by the fact that the QCM-D signal stems from the protein molecules and the trapped water.…”
Section: Introductionmentioning
confidence: 98%
“…The amount of the latter is a complicated function of the substrate topology (roughness), protein molecule shape and conformations, monolayer coverage and molecule orientation, flow rate, viscosity of the monolayer, oscillation frequency, etc. [23][24][25]27,28]. Therefore, the deconvolution of the primary QCM signal aimed at deriving the 'dry' mass of the protein cannot be done ab initio without accepting empirical models of the monolayer structure [29].…”
Section: Introductionmentioning
confidence: 98%
“…It is, however, a model protein for molecular adhesion studies having a tendency to adsorb non-specifically to a wide range of surfaces, including the so-called non-fouling chemistries like poly(ethylene glycol) (PEG) [6][7][8][9]. The PEG surface functionality is strongly hydrophilic, both in its interior and on its surface, retaining a hydration layer of electrostatically bound water molecules at the surface interface and along the chain that makes adsorption impossible for molecules not specifically adapted to the task.…”
Section: Introductionmentioning
confidence: 99%